British Society of Echocardiography Departmental Accreditation Standards 2019 with input from the Intensive Care Society. Issue 1 (March 2020) - Ritzmann, Sarah; Baker, Stephanie; Peck, Marcus; Ingram, Tom E; Allen, Jane; Duffy, Laura; Steeds, Richard P; Houghton, Andrew; Elkington, Andrew; Bual, Nina; Huggett, Robert; Pearce, Keith; et al.
Abstract : This article sets out a summary of standards for departmental accreditation set by the British Society of Echocardiography (BSE) Departmental Accreditation Committee. Full accreditation standards are available at www.bsecho.org . The BSE were the first national organisation to establish a quality standards framework for departments that support the practice of individual echocardiographers. This is an updated version which recognises that, not only should all echocardiographers be individually accredited as competent to practice, but that departments also need to be well organised and have the facilities, equipment and processes to ensure the services they deliver are of an appropriate clinical standard. In combination with individual accreditation, departmental accreditation lays down standards to help ensure safe and effective patient care. These standards supersede the 2012 BSE Departmental Accreditation Standards. Standards are set to cover all potential areas of practice, including transthoracic (level 2) echocardiography, transoesophageal echocardiography, stress echocardiography, training, and emergency (level 1) echocardiography. The emergency echocardiography standard is a new addition to departmental accreditation and has been developed with input from the Intensive Care Society.